Estimation of in-plane shear capacity of confined masonry walls with and without openings using strut-and-tie analysis. (1st June 2019) - Tripathy, D.; Singhal, V.
Highlights: Strut-and-tie method (STM) proposed for estimating in-plane strength of CM wall. Parametric non-linear FE analysis used to establish limiting strut capacity. Proposed STM closely predicts shear strength of walls with and without openings. Abstract: Strut-and-tie analysis is popularly used for the design of shear critical structures and can be applicable for the analysis of confined masonry (CM) walls, which often behave as shear walls. Properties of ties in a strut-and-tie model of CM wall can be simply computed from the yield strength of longitudinal reinforcement whereas that of masonry compression strut may depend on various parameters such as its aspect ratio, the strength of masonry and concrete. A non-linear parametric analysis was performed on more than 200 finite element models to understand the behaviour of masonry strut and a stepwise methodology for the formulation of the strut-and-tie model was proposed for CM walls. The proposed strut-and-tie method was validated by various experimental studies available in the literature. The developed strut-and-tie models consistently provided good predictions for the in-plane capacity of CM walls with and without openings when compared to the experimental results.